Conventional Ultrasonography: A Remarkable Tool in Early Detection of Benign Ovarian Lesions in Comparison to Gold Standard MRI - Jabeen, Naila; Walid, Ayesha; Rasheed, Binish; Naz, Nasreen; Rahim, Anila; Siddiqui, Rabeeya Qutub uddin (Pakistan Armed Forces Medical Journal, 2023)
Objective: This study aimed to assess the efficiency of ultrasonography in the accurate diagnosis of benign ovarian lesions as compared to the gold standard Magnetic Resonance Imaging (MRI).Study Design: Prospective analytical cross-sectional study.Place and Duration of Study: Dow Institute of Radiology, Dow University of health sciences (DUHS), OJHA Campus, Karachi, Pakistan, from Jun 2018 to Nov 2019Methodology: The consecutive sampling technique was used to recruit the patients. The frequency and percentage, and mean and standard deviation were calculated for qualitative and quantitative variables, respectively. The p-value